Ageing in a Long-term Regeneration Neighbourhood: A Disruptive Experience or Successful Ageing in Place? - Reinout Kleinhans; Lex Veldboer; Sylvia Jansen; Maarten van Ham (Institute for the Study of Labor (IZA), 2014)
The aging population of European cities raises enormous challenges with regard to employment, pensions, health care and other age-related services. The housing preferences of the aging population are changing rapidly where more and more people want to live independent lives for as long as possible. At the same time governments need to reduce the costs of expensive institutionalized care. A precondition for 'ageing in place' is that elderly people perceive their neighbourhoods as familiar and safe places. In the Netherlands, many neighbourhoods with a rapidly ageing population have been subject to urban regeneration policies. Hence, an important question is to what extent these policies affect the housing situation, social support networks and socioeconomic position of elderly people, because these factors strongly assist the ability of elderly people to live independently. We answer this question through the analysis of a small but unique panel data set with 2007 and 2012 measurements from Hoogvliet, a district of Rotterdam. Contrary to claims about large, disrupting impacts of urban regeneration, the results show that even in times of economic crisis regeneration in Hoogvliet has enabled 'ageing in place'. There appears no relationship between the Hoogvliet policies and changes in income of elderly people and their ability to get by financially. Those who have moved home often report regeneration benefits, mostly related to accessing better quality housing in the same area. Finally, we found no clear evidence of decreased social support or increased loneliness through regeneration-induced disruption of social networks.
Keywords: J14; O18; R23; 330; ageing in place; urban regeneration; social networks; social support; loneliness; Rotterdam